THE EFFECT OF THE REALISTIC MATHEMATIC EDUCATION (RME) APPROACH ON SPACIOUS FIGURES TO IMPROVE STUDENTS' CONCEPTUAL UNDERSTANDING AND LEARNING ACHIEVEMENT - Simanjorang, Arifin Kharisma (Journal of Innovation in Research, Education and Culture (JIREC), 2025)
The Effect of Realistic Mathematics Education (RME) Approach on Solid Geometry Material to Improve Students' Conceptual Understanding and Learning Achievement. Thesis. Mathematics Education Study Program. Faculty of Teacher Training and Education. Muhammadiyah University of North Sumatra.The purpose of this study is to determine the Effect of Realistic Mathematics Education (RME) Approach on Solid Geometry Material to Improve Students' Conceptual Understanding and Learning Achievement. The population in this study is all grade X students of SMK TRITELCH INFORMATIKA MELDAN in the 2023/2024 academic year consisting of one class. The sample of this research is class X with a total of 25 people from various classes of ELKSPERRIMELn with the Realistic Mathematics ELducation (RMEL) approach. This research took place from August 22, 2024 – September 5, 2024. Data collection in this research uses TEST techniques. The first TEST uses pretest and the second uses posttest. The results of the pretest scores of all students are <75 (did not pass) and the results of the posttest of all students are >75 (passed). From the results of this study, it can be concluded that there is an influence of the Realistic Mathelmatics ELducation (RMEL) attachment on the understanding of the concept and learning achievement of mathematics students of grade X SMK TRITELCH INFORMATIKA MELDAN. Keywords: Realistic Mathelmatics ELducation (RMEL) attachment, on the understanding of the concept and learning achievement of students.